The Influence of Public Service Advertisement Media on Persuasive Text Writing Skills in Grade VIII Students of Mts Darussalam, Kasomalang, Subang - Cucun Kurnia; Irpan Maulana; Desti Kusmayanti (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study aims to determine the influence of public service advertisement media on persuasive text writing skills at MTs PP Darussalam, Kasomalang, Subang. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of 44 students divided into an experimental class (using advertisement media) and a control class (using the lecture method). The results showed a significant increase in the experimental class, with a posttest average reaching 78.00, compared to the control class which only reached 54.91. Statistical analysis through the Mann-Whitney Test produced a significance value of 0.000 < 0.05. Additionally, the N-Gain test demonstrated the effectiveness of the experimental class at 68% compared to the control class at only 30%. It is concluded that the use of public service advertisement media has a positive influence on learning outcomes. This media proved effective in increasing students' understanding, motivation, and interest in learning while creating an enjoyable atmosphere, unlike the lecture method which tends to be boring and makes students less enthusiastic. Keywords: Public Service Advertisement Media, Writing Skills, Persuasive Text Abstrak: Penelitian ini bertujuan mengetahui pengaruh media iklan layanan masyarakat terhadap keterampilan menulis teks persuasi di MTs PP Darussalam, Kasomalang, Subang. Metode penelitian menggunakan pendekatan kuantitatif dengan desain quasi experimental. Sampel terdiri dari 44 peserta didik yang dibagi menjadi kelas eksperimen (media iklan) dan kelas kontrol (metode ceramah). Hasil penelitian menunjukkan peningkatan signifikan pada kelas eksperimen dengan rata-rata posttest mencapai 78,00, berbanding jauh dengan kelas kontrol yang hanya mencapai 54,91. Analisis statistik melalui Uji Mann-Whitney menghasilkan nilai signifikansi 0,000 < 0,05. Selain itu, uji N-Gain menunjukkan efektivitas kelas eksperimen sebesar 68% dibandingkan kelas kontrol yang hanya 30%. Disimpulkan bahwa penggunaan media iklan layanan masyarakat berpengaruh positif terhadap hasil belajar. Media ini terbukti efektif meningkatkan pemahaman, motivasi, dan minat belajar siswa serta menciptakan suasana menyenangkan, berbeda dengan metode ceramah yang cenderung membosankan dan membuat siswa kurang antusias. Kata Kunci: Media Iklan Layanan Masyarakat, Keterampilan Menulis, Teks Persuasi